UPAYA PEMERINTAH KAMPUNG ADAT KUALA GASIB KECAMATAN KOTO GASIB KABUPATEN SIAK DALAM MELESTARIKAN ADAT ISTIADAT TAHUN 2015-2016 - Panca Agustina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research based on changes in the status of the Kampung into Kampung Adat in Siak Regency stated in Regional Regulationnumber 2th, 2016 about change of name Kampung into Kampung Adat. One of the Kampung who changed his status is Kampung Kuala Gasib in Koto Gasib. Kampung Kuala Gasib located on the outskirts of the cross street of Sumatra which makes many migrants from other regions who began to settle in that kampung. That thing makes the tradition and the culture of native range is abandonedandunknown by the younger generation.The purposes of Research is: first, to know the Government's efforts of Kampung Adat Kuala Gasib Sub Koto Gasib Siak Regency in preserving the customs in 2015-2016. Second, to find out the factors who impede the efforts preservation of customs. The type of research is descriptive with qualitative research methods. The location of the research carried out at Kampung Adat Kuala Gasib Sub Koto Gasib Siak Regency. The Technique of data collection byconducting interviews, observation and documentation. And data analysis is using by qualitative data analysis techniques.The results of this research are the Government of Kampung Adat Kuala Gasib not yet afford maximum preservation. As for the main impede of factor is yet to discharge theregister numbering or code of Kampung Adat from the Central Government and not yet existence of the local regulations more aboutKampung Adat.Keywords: Government of Kampung Adat Kuala Gasib and Customs